Problem of Thermal Shock on the Basis of Hyperbolic Equations - E. M. Kartashov; O. I. Remizova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains the formulation and solution of the problem of dynamic thermoelasticity with due account of final heat velocity in material. On the basis of the obtained calculated expressions for determination of temperature stresses an influence of final heat velocity on thermally stressed state of material under various types of heat loading has been analyzed in the paper.